Additive manufacturing of multifunctional composite structures - Gackowski, Bartosz Mikolaj (Nanyang Technological University, 2023)
Additive manufacturing has the potential to influence a broad array of engineering domains through its ability to create materials with tailored properties and functionalities. Although the capabilities to print fast, reliably, and with various materials have progressed dramatically in recent years, the aim of printing ‘smart’ composite materials has not yet been fully achieved. This thesis seeks to establish an alternative way of additive manufacturing polymer composites by embedding thin films containing carbon nanotubes and carbon fibre additives using a novel hybrid layer-by-layer deposition technique. The proposed 3D printer deposits a suspension of nanotubes in a liquid medium onto polymer substrates, which later self-assemble into a thin film known as a buckypaper. Short carbon fibres can be combined with suspended nanotubes to create hybrid buckypapers (HBPs). Their size is only limited by the manufacturing bed, and their weight percentage in a composite can be altered in three ways: by modifying the composition of suspensions, the thickness of HBPs, and the height of polymer layers. This thesis investigates the interplay between the number and composition of these thin films and their ability to be utilized for tailoring mechanical properties, out-of-autoclave post-processing by Joule heating, de-icing, anti-icing, and damage detection. Initially, a high number of buckypapers in a composite resulted in decreased interlaminar shear strength, most likely caused by delamination at the buckypaper-polymer interfaces. Thermoplastic (polyurethane) or thermoset (epoxy) binders were added to the suspensions to alleviate the bonding issue. After vacuum-bagging to melt or post-cure the binders, the porosity of 3D-printed composites was reduced from 4.8% to 0.5%. The weight fraction and type of binder modulated the microstructure of the hybrid buckypapers, as well as the resulting mechanical and electrical properties of the composites. Furthermore, chemical functionalization of the conductive fillers increased the adhesion between the constituents of hybrid buckypapers, as measured by interfacial shear strength testing. This approach preserves the design freedom and electrical properties of carbon nanotubes. Thus, the 3D-printed composites with HBP were used for out-of-autoclave post-processing by embedding resistive heaters inside the composite, which was then heated by Joule heating during vacuum-bagging. The Joule heating effect remained effective when the temperature of the environment was reduced to 0°C, -20°C, -40°C, and -60°C in a thermal chamber, generating over 100°C on the top surface in each case. The piezoresistive property of carbon nanotubes was used to detect damage during tensile, flexural, and impact testing. The location and shape of the 3D-printed conductive paths allowed for the detection of local or global damage inside the composite structure. Overall, this thesis lays the groundwork for the cost-effective incorporation of two-dimensional and three-dimensional conductive paths inside a polymer matrix of any size and shape. The composition, geometry, and location of these paths inside a printed material can be freely customized for a specific purpose. As a result, the method can be expanded in the future for various other applications, including energy and memory storage, photovoltaics, and chemical sensors, among many others.